Limitations associated with transcranial direct current stimulation for enhancement: considerations of performance tradeoffs in active-duty Soldiers - Duffy, Michelle J.; Feltman, Kathryn A.; Kelley, Amanda M.; Mackie, Ryan (Frontiers in Human Neuroscience, 2024)
Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation method, popular due to its low cost, ease-of-application, and portability. As such, it has gained traction in examining its potential for cognitive enhancement in a diverse range of populations, including active-duty military. However, current literature presents mixed results regarding its efficacy and limited evaluations of possible undesirable side-effects (such as degradation to cognitive processes). To further examine its potential for enhancing cognition, a double-blind, randomized, sham-controlled, within-subjects design, was used to evaluate both online active-anodal and -cathodal on several cognitive tasks administered. Potential undesirable side effects related to mood, sleepiness, and cognitive performance, were also assessed. Active tDCS was applied for 30 min, using 2 mA, to the left dorsolateral prefrontal cortex with an extracephalic reference placed on the contralateral arm of 27 (14 males) active-duty Soldiers. We report mixed results. Specifically, we found improvements in sustained attention (active-anodal) for males in reaction time (p = 0.024, ηp 2 = 0.16) and for sensitivity index in females (p = 0.013, η p 2 = 0.18). In addition, we found faster reaction time (p = 0.034, ηp 2 = 0.15) and increased accuracy (p = 0.029, ηp 2 = 0.16) associated with executive function (active-anodal and -cathodal), and worsened working memory performance (active-cathodal; p = 0.008, ηp 2 = 0.18). Additionally, we found increased risk-taking with active-anodal (p = 0.001, ηp 2 = 0.33). tDCS may hold promise as a method for cognitive enhancement, as evidenced by our findings related to sustained attention and executive function. However, we caution that further study is required to better understand additional parameters and limitations that may explain results, as our study only focused on anode vs cathode stimulation. Risk-taking was examined secondary to our main interests which warrants further experimental investigation isolating potential tradeoffs that may be associated with tDCS simulation.